Histopathological Feature On Chronic Or Delayed Progression Epidural Hematoma - Feda Anisah Makkiyah (ANATOMICA MEDICAL JOURNAL | AMJ, 2023)
The incidence of chronic epidural haematoma (CEDH) is uncommon. The exact definition of the time and the guideline is not established until now. Meanwhile, there is also another entity, delayed progression of epidural hematoma (DEDH), which is also a  rare condition and some authors included it as  CEDH. Method: We present a case report here of a patient with no initial imaging taken, because of minimal symptoms. Because the persistence of headache, after one month, head CT scan was performed, and patient underwent craniotomy evacuation procedure. There was pathologic examination to differentiate diagnosis. Results: The pathological view showed that there was fibrotic tissue, blood vessels, multinucleated giant cells, hemosiderophages, lymphocytes, chronic inflammation cell, small to medium sized blood vessels and trabeculae of bone. Conclusion: The definite diagnosis will be established by the histopathology. Here, we present a CEDH case with the histopathology result. The support of histopathology generates clear images of the entity.Keywords: CEDH, DEDH, histopathology view